MAKING EFL INSTRUCTION MORE CLT-ORIENTED THROUGH INDIVIDUAL ACCOUNTABILITY IN COOPERATIVE LEARNING - Astuti, Puji; Lammers, Jayne C. (TEFLIN Journal, 2017)
This article attempts to add to the literature supporting Communicative Language Teaching (CLT) by proposing the use of Cooperative Learning (CL), specifically focusing on the enactment of a key principle of CL, i.e., individual accountability. It illustrates how to train students on CL and its individual accountability work and demonstrates how activities involved in individual accountability, i.e., individual students’ performance(s) and peer interaction, can accommodate the teaching of the four language skills and components. We argue that these activities promote learners’ use of and meaning making in English and thus recommend teachers, especially those new to CL, follow the procedure of CL techniques exactly as described so that language learning in their classrooms goes in the direction of attaining improved communicative competence”the goal of CLT.